Human TYRP1: Two functions for a single gene?. (16th February 2021) - Gautron, Arthur; Migault, Mélodie; Bachelot, Laura; Corre, Sébastien; Galibert, Marie‐Dominique; Gilot, David
Abstract: In the animal kingdom, skin pigmentation is highly variable between species, and it contributes to phenotypes. In humans, skin pigmentation plays a part in sun protection. Skin pigmentation depends on the ratio of the two pigments pheomelanin and eumelanin, both synthesized by a specialized cell population, the melanocytes. In this review, we explore one important factor in pigmentation: the tyrosinase‐related protein 1 ( TYRP1 ) gene which is involved in eumelanin synthesis via the TYRP1 protein. Counterintuitively, high TYRP1 mRNA expression is associated with a poor clinical outcome for patients with metastatic melanomas. Recently, we were able to explain this unexpected TYRP1 function by demonstrating that TYRP1 mRNA sequesters microRNA‐16, a tumor suppressor miRNA. Here, we focus on actors influencing TYRP1 mRNA abundance, particularly transcription factors, single nucleotide polymorphisms (SNPs), and miRNAs, as they all dictate the indirect oncogenic activity of TYRP1 .